Recent advances in the transcriptional regulation of the flavonoid biosynthetic pathway - Hichri, Imène; Bogs, Jochen (The journal of experimental botany, 2011)
Flavonoids are secondary metabolites involved in several aspects of plant development and defence. They colour fruits and flowers, favouring seed and pollen dispersal, and contribute to plant adaptation to environmental conditions such as cold or UV stresses, and pathogen attacks. Because they affect the quality of flowers (for horticulture), fruits and vegetables, and their derivatives (colour, aroma, stringency, etc.), flavonoids have a high economic value. Furthermore, these compounds possess pharmaceutical properties extremely attractive for human health. Thanks to easily detectable mutant phenotypes, such as modification of petal pigmentation and seeds exhibiting transparent testa, the enzymes involved in the flavonoid biosynthetic pathway have been characterized in several plant species. Conserved features as well as specific differences have been described. Regulation of structural gene expression appears tightly organized in a spatial and temporal way during plant development, and is orchestrated by a ternary complex involving transcription factors from the R2R3-MYB, basic helix-loop-helix (bHLH), and WD40 classes. This MYB-bHLH-WD40 (MBW) complex regulates the genes that encode enzymes specifically involved in the late steps of the pathway leading to the biosynthesis of anthocyanins and condensed tannins. Although several genes encoding transcription factors from these three families have been identified, many gaps remain in our understanding of the regulation of this biosynthetic pathway, especially about the respective roles of bHLH and WD40 proteins. A better knowledge of the regulatory mechanisms of the flavonoid pathway is likely to favour the development of new biotechnological tools for the generation of value-added plants with optimized flavonoid content.